“Accompanying the path” as relationship in Alzheimer`s disease (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The author shows Alzheimer’s disease as an example of existential struggles constantly present in human life, especially in context of family carers. In this article relation in Alzheimer`s disease is described as “accompanying the path”, which helps to face with great difficulties of this disease. The author characterized “Accompanying the path” as several relations such as geragogical, social, personal, relation with Other person, relation “to be”. Analyzed experiences of three family carers of Alzheimer`s disease patients, shows several dimensions and principles of “accompanying the path” relation. Those are: personal dimension (personalistic) – which is rule of respecting patient as an human being (person); emotional dimension – rule of creating and maintaining positive emotions; community dimension – obligation to build community bounders within family and social environment of patient; communication dimension – obligation to constant communication with a patient, considering understanding and conversations.